1992
DOI: 10.1007/bf02164640
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic relations between eugnathies, malocclusions from the type of class II/1 and class III and changes of the topography of the cervical spine studied on the lateral cephalogram

Abstract: Relations are discussed between malocclusions and changes of the vertebral spine. It was the aim of our investigations to disclose the causal relations between changes of the position of the cervical spine and class-II/1 anomalies (49 patients), class-III anomalies (28 patients), and eugnathic maxillary conditions (50 children). 127 lateral cephalograms of the untreated 63 boys and 64 girls at the age from six to 13 years were evaluated according to 24 orthodontic and 25 orthopedic characteristics. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Regarding the relationship of the cervical spine and the jaw position, there are several studies describing the jaw position and the spine inclination on the basis of the analysis of lateral radiographs. [8][9][10]12,13,31,32 Here, the literature's postulation regarding the use of the upper spine section to substantiated examination procedures for the valid verification of the body posture has been fulfilled. 4,7 As already mentioned by Korbmacher et al, 4 there are no studies on the relationship of the jaw position to the body posture regarding spine sections below the cervical spine that use substantiated study procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship of the cervical spine and the jaw position, there are several studies describing the jaw position and the spine inclination on the basis of the analysis of lateral radiographs. [8][9][10]12,13,31,32 Here, the literature's postulation regarding the use of the upper spine section to substantiated examination procedures for the valid verification of the body posture has been fulfilled. 4,7 As already mentioned by Korbmacher et al, 4 there are no studies on the relationship of the jaw position to the body posture regarding spine sections below the cervical spine that use substantiated study procedures.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies negate the existence of correlations between specific orthopedic findings with certain jaw positions. 12, 13 Michelotti et al 7 postulated that even though there are descriptions of an interdependence of the upper cervical spine and the jaw position in the literature, there is no evidence of such a relationship in further caudally located spine sections.…”
Section: Introductionmentioning
confidence: 99%
“…One point open to discussion, however, is that according to scientific evidence the degree of lordosis of the cervical spine declines with increasing age [18]. However, some interdisciplinary studies refute the hypothesis of the existence of Angle Class-specific orthopedic findings [21,64,65]. These studies found no statistically significant correlations between orthopedic findings and sagittal jaw relationship.…”
Section: Angle Class-specific Findingsmentioning
confidence: 99%
“…Es existieren jedoch auch interdisziplinär geführte klinische Studien [21,64,65], die die Hypothese des Vorhandenseins Angle-Klasse-spezifischer orthopädischer Befunde widerlegen. In diesen Untersuchungen konnten keine statistisch signifikanten Korrelationen zwischen orthopädischen Befunden und sagittaler Bisslageanomalie ermittelt werden.…”
Section: Soft Tissueunclassified